Container architecture and landscape: a brand new view through Site-Specific Art - Cabrera Vergara, María (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2016)
Over the last decades, the phenomenon of container architecture has generated constant and controversial debates. Many consider it as a temporary practice, even outmoded today, while others do not even recognize it as a form of architecture. However, its current dissemination is undeniable, and it deserves a careful analysis.Through the study of three recent examples, and their comparison with three iconic works of Site Specific Art, this paper intends to invite the reader to address these architectures with a new gaze, and to elucidate the reasons why these objects alien to any site, can constitute architectural proposals capable of establishing a true communion with the landscape.